Synthesis and characterization of magnesium borate minerals of admontite and mcallisterite obtained via ultrasonic mixing of magnesium oxide and various sources of boron: a novel method - Kipcak, Azmi Seyhun; Derun, Emek Moroydor; Piskin, Sabriye (Tubitak Scientific & Technological Research Council Turkey, 2014)
Magnesium borates can be used as detergent compounds or hydrocarbon catalyzers and in the ceramics industry for superconductor material manufacture owing to their high elastic coefficient and resistance to corrosion at high temperatures. In the present study, the synthesis of magnesium borate was facilitated via a novel ultrasonic method of mixing and the identification and characterization of the material were carried out via X-Ray diffraction (XRD), Fourier transform infrared (FT-IR), and Raman spectroscopies, and the B2O3 content was determined through titration. The surface morphology was investigated using scanning electron microscopy (SEM). The results of the XRD analysis identified the synthesized borate compounds as admontite [MgO(B2O3)(3)center dot 7(H2O)], with powder diffraction file (pdf) no 01-076-0540, and mcallisterite [Mg-2(B6O7(OH)(6))(2)center dot 9(H2O)], with pdf no 01-070-1902. The FT-IR and Raman spectra of the obtained samples were similar, with characteristic magnesium borate bands observed in both the infrared and visible regions. The results of the B2O3 content analysis were in compliance with the literature. The investigation of the SEM images indicated that nanoscale minerals with a reaction efficiency ranging between 69% and 82% were obtained.
Keywords: Magnesium borate; admontite; mcallisterite; ultrasonic mixing; DEHYDRATION KINETICS; ULEXITE; Chemistry; Engineering